Ulumul Qur’an : Keadilan Organisasional Dalam Al Quran Dan Implikasiny - Herlin Yulianti; Darwis Hude (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This paper examines organizational justice from a Qur’anic perspective and its implications for the management of Islamic educational institutions. The main problem addressed in this study concerns how the concept of justice in the Qur’an can be understood through the approach of Qur’anic studies and applied as a foundation for managing Islamic educational institutions. This study aims to explore the principles of Qur’anic justice and their relevance to organizational justice in educational management. The research employs a qualitative library-based method by analyzing Qur’anic verses, classical and contemporary Qur’anic commentaries, and scholarly works on Qur’anic studies and Islamic educational management. Data are analyzed thematically by considering linguistic aspects, the context of revelation, and interrelationships among verses. The findings indicate that the Qur’an conceptualizes justice as proportionality, objectivity, and trustworthiness in managing institutional relationships. These principles correspond substantially with the concept of organizational justice in modern management. The study concludes that Qur’anic justice can serve as an ethical and normative foundation for the management of Islamic educational institutions in order to promote fair, professional, and welfare-oriented governance